52.3: Development of Back‐channel‐etched TFT Using C‐Axis Aligned Crystalline In‐Ga‐Zn‐Oxide. Issue 1 (1st July 2013) - Koezuka, Junichi; Okazaki, Kenichi; Hirohashi, Takuya; Takahashi, Masahiro; Adachi, Shunsuke; Tsubuku, Masashi; Yamazaki, Shunpei; Kanzaki, Yohsuke; Matsukizono, Hiroshi; Kaneko, Seiji; Mori, Shigeyasu; Matsuo, Takuya
Abstract We have fabricated a back‐channel‐etched TFT using the CAAC‐IGZO film that we developed. As a factor of success in manufacturing stable back‐channel‐etched TFTs, it is considered that CAAC‐IGZO has a strong structure because of its crystallinity. For verification, we have compared the cohesive energy of c‐IGZO and that of a‐IGZO.